(untitled) (European Journal of Pure and Applied Mathematics, 2026)
In Almost Distributive Lattices (ADLs), the idea of Q-ideals is defined, and various properties of these ideals are investigated. characterizations are established that determine precisely when a λ-ideal in an ADL qualifies as a Q-ideal. Furthermore, equivalent conditions are established for when an E-ideal in an ADL can be recognized as a Q-ideal. The characterization of E-complemented ADLs is achieved through the use of Q-ideals